Interface Shear Behavior of Sensitive Marine Clays --Leda Clay - Taha, Ahmed M (University of Ottawa (Canada), 2010)
Leda clay, which is a type of sensitive marine clay in Canada, is a hazardous soil that could undergo sudden collapse and flow upon wetting and remolding. This type of soil causes many landslide disasters and foundation damage. The existence of Leda clay at or near the proximities of developed cities makes it challenging for infrastructure expansion, and therefore, challenging for geotechnical engineers. At the location where this sensitive marine clay exists, many foundation designers have adopted the use of deep foundations, such as pile foundations to support heavy structures. The shear behavior and strength parameters at the interface between the (friction) pile and soil are key design parameters. A sufficient knowledge of these interface shear behaviors and strength parameters is also essential for the safe and cost-effective design of several other geotechnical structures (e.g., retaining walls, reinforced soils, and buried structures). However, no studies have yet been implemented on the interface shear behavior between Leda clay and structural material. There is therefore, a need to generate more knowledge about the interface shear behavior of Leda clay. This thesis deals with an experimental study of the shear behavior at the interface between Leda clay and structural material, such as steel and concrete. The effects of several factors, such as surface roughness of the construction material, Leda clay's overconsolidation ratio (OCR), saturation degree, density, and salt content on interface shear behavior are also investigated. Laboratory tests have been carried out by using an automatic direct shear machine connected to a linear variable differential transformer (LVDT), loading cell and a data logging system. The results of the interface shear tests show that under consolidated drained (CD) and saturated conditions, the interface friction angle increases with an increase in the clay's OCR. The results also indicate that increasing the salinity of Leda clay's pore water enhances its frictional resistance at the interface. Furthermore, the results reveal that Leda clay with a higher dry density shows higher interface shear resistance. On the other hand, the results also show that the interface shear resistance decreases as the degree of saturation of the Leda clay increases.
Keywords: Engineering, Civil.